PEREMPUAN DI SEKTOR PUBLIK - Leny Nofianti (Marwah: Jurnal Perempuan, Agama dan Jender, 2016)
The productive role that is often referred to the role of the public sector by women are in formal or informal sectors. Women working in the public sector generally have an education that tend to be high. Women want to realize the education she receives in terms of work. Women apply that knowledge in work. Work is an achievement to be able to improve the lives of humans. This paper analyzes how the role of women working in the public sector and the problems they face with multiple roles. Gender issues that arise in the formal sector is that most women are in the lower position rather than men.